Effects of participation in cooperatives on the cultivated land quality protection behavior of grain family farms: evidence from China - Duan, Wei; Luo, Guangqiang (Frontiers in Sustainable Food Systems, 2024)
Introduction The implementation of cultivated land quality protection is fundamental for ensuring the sustainable use of land resources, and it is the inevitable choice for maintaining the balance of agricultural ecology and promoting the long-term healthy development of agriculture. Methods Based on survey data from 927 grain family farms in 13 major grain-producing areas in China, this paper empirically tests the effects of participation in cooperatives on the cultivated land quality protection behavior of grain family farms by using a logit model, an ordered probit model and the propensity score matching method. Results The results show that participation in cooperatives has a significant positive effect on the implementation of cultivated land quality protection behavior and the degree of cultivated land quality protection of grain family farms. A series of robustness tests reveals that the conclusion of the study does not change. Heterogeneity analysis reveals that the probability of implementing cultivated land quality protection behavior significantly increased, and the effect was greater for farms with the younger farmers, farmers of lower education level, farmers of non-party members, larger scale of operation, longer establishment years, larger labor force, or provincial demonstration. Discussion On this basis, we should vigorously support and guide grain family farms to participate in cooperatives, give full play to the advantages of cooperatives, effectively encourage farms to implement cultivated land quality protection behavior, and promote sustainable agricultural development.